Pemberantasan Buta Aksara Al-Qur’an Melalui Program Kaderisasi Guru Ngaji - Syaefulloh, Syaefulloh; Wulandari, Dewi (E-Jurnal Aksioma Ad Diniyyah : The Indonesian Journal of Islamic Studies, 2024)
Illiteracy of the Koran is still a serious problem for the Indonesian Muslim community. The results of several studies show an increase in the level of Koran illiteracy in Indonesia which is caused by several factors, including the scarcity of Koran teachers. Several efforts have been made to eliminate or reduce the level of illiteracy of the Koran, one of which is through the Koran Teacher Cadre Program. This article aims to reveal and identify the concept of Koran teacher cadre formation, how it is implemented and what impact it has on the level of illiteracy of the Koran. The results of the research show that the Koran teacher cadre program is a special program that prepares quality human resources in the field of Al-Qur'an so that they are able to teach Al-Qur'an easily and pleasantly so that it can increase the number of people who learn Al-Qur'an and are expected to be able to reducing the level of illiteracy of the Koran. The Reciting Teacher Cadreship Program consists of; 1) Socialization, 2) Tashih, 3) Tahsin, 4) Certification, 5) Implementation Assistance, 6) Monitoring, 7) Evaluation and 8) Increasing competency through strengthening recitations, tahfizh Al-Qur'an, recitation study, talaqqi taking sanad and qiroat. This program has had an impact on the birth of many reliable and competent Al-Qur'an teachers who have contributed by opening Al-Qur'an classes in their respective regions and the birth of students who are able to read the Al-Qur'an well, correctly, tartil, memorize several juz and contribute to reducing the level of illiteracy of the Al-Qur'an.. Keywords: Illiteracy, cadre formation, Koran teacher